EVOLUTION OF THE CONCEPT OF «WHITE MAN'S BURDEN» IN THE BRITISH CINEMA OF 20TH CENTURY - E. E. Ibrayev (Vestnik MGIMO-Universiteta)
The article discusses the features of the evolution on the silver screen so-called "white man's burden" or "civilizing mission" in the British colonies of the British Empire. The means of research were British feature films 1930-1980-ies. Using the author's methods of analysis of the ideological content of tapes and the context of their stories, it became clear that the idea of the "burden of the white" changed not only under the influence of the current socio-political situation in the metropolis and in the world, but also to a large extent transformed under the influence of highly artistic works of British directors each of which sought to bring to the story of the "civilizing mission" own view and vision to such a feature of the existence of the British Empire. The first feature films dedicated to the colonial subjects, by chance came the period of the ideological crisis of the empire in 1930, carried a powerful message of world film audience, the essence of which was the fact that Britain bears colonies only "good and justice" that without imperial province will remain forever languish in "darkness and ignorance." These films have reconciled a few British viewers with the idea of the need to preserve the empire. After the collapse of the colonial system there are films that criticize the cultural expansion of Europeans in the countries of Asia and Africa. The emphasis in these films was placed on the British arrogance and cruelty to the autochthonous peoples. The apogee evolution "burden of the white" reached in 1980, when Britain itself was to form multicultural society. The films of the decade have been devoted to the complete discrediting of the "civilizing mission" and recognize their mistakes in the relationship with the population of the colonies.